Para além do universalismo e do particularismo: os Direitos Humanos como núcleo comum da resistência - Deo Campos Dutra (Revista Interdisciplinar de Direito, 2018)
The main purpose of this work is to provide an alternative for the construction of a proposal for Human Rights and a minimum content of human dignity that is committed to overcoming the classic debate based on the dichotomy between universalism and particularism. In this sense, the theoretical key used is present in the work of Spanish professor Joaquin Herrera Flores. In parallel with Antonio Negri, we offer the results of this Human Rights perspective as a theoretical source strong enough to contribute to the construction of a strengthened “Antipower” capable of effectively confronting the complex system called Power described by an Italian philosopher. In order to reach our two main objectives, we adopted bibliographical and quantitative research, embracing a descriptive and analytical approach as methodology for this work.